Migration and Remittances Factbook 2008 - Ratha, Dilip K. (The World Bank, 2008)
This book contains statistical snapshots for 195 countries and 13 regional and income groups. The 200+ tables, each focused on one country, region, or income group, explore immigration, emigration and skilled emigration, and inward and outward remittance flows. Summary reports on the top 10 countries in each category are also included